Pemetaan Posisi Keunggulan Mutu Layanan Daya Saing Destinasi Wisata Kota Pekalongan Berbasis Inovasi Komunitas - Adhi Pratomo, Sigit; Sri Nugroho, Arif Julianto; Tasari; Haris, Abdul; Jati, Agung Nugroho; Santoso, Agus (Cattleya Darmaya Fortuna, 2024)
This study aims the position competitive exellence tourism destination in Pekalongan. The research method used quantitatvive model. The sampling model used purposive sampling with 120 respondents. Research atribut adopt from Cooper’s with attraction, accesbility, amenity and ancilliary. The tes model used MDS Multivariate. Kampoeng Batik Pesindon and Kampoeng Batik Kauman is in a relative exellent quadrant position compared to the other three tourism destination .Pasir Kencana and Wisata Bahari occupy a challenger position. The research activities is to propose marketing strategy solution s to win competition among tourism destinantion exellence in the future.